2009
DOI: 10.1007/s00535-008-2278-2
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate increases risk of gastroduodenal ulcer in rheumatoid arthritis patients on long-term nonsteroidal antiinflammatory drug therapy

Abstract: Bisphosphonate co-therapy as well as advanced age and smoking was found to be a significant risk factor in PU, while co-therapies of standard-dose H2RA or PPI/PG proved effective in preventing PU in Japanese RA patients on long-term NSAID treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Consistently with our findings, observational studies (OSs) did not found evidence of increased UGIC risk among BP users [15], [16], [19]. However, conversely to our results, BPs – NSAIDs co-therapy has been found to increase the UGIC risk [18], [19]. It should be noticed, that our findings were obtained by contrasting current and past use of BPs, rather than BPs use vs. placebo (or vs. no use) as in RCTs (or in OSs).…”
Section: Discussionsupporting
confidence: 91%
“…Consistently with our findings, observational studies (OSs) did not found evidence of increased UGIC risk among BP users [15], [16], [19]. However, conversely to our results, BPs – NSAIDs co-therapy has been found to increase the UGIC risk [18], [19]. It should be noticed, that our findings were obtained by contrasting current and past use of BPs, rather than BPs use vs. placebo (or vs. no use) as in RCTs (or in OSs).…”
Section: Discussionsupporting
confidence: 91%
“…A recent cross-sectional endoscopic analysis conducted in 2006 [29] has shown that 62.8% of the patients who regularly took NSAIDs had gastroduodenal injuries, even though loxoprofen was prescribed as the first choice of NSAID for long-term NSAID users. According to a recent report, the incidence of NSAID-associated gastroduodenal ulcers is higher than 20% in Japanese RA outpatients having taken NSAIDs for 3 or more months [30]. In the recent and first epidemiological study in Japan [31], the risks of upper GI bleeding have been shown to be about 6 and 11 times higher, respectively, in subjects taking loxoprofen and diclofenac than in subjects not taking NSAIDs.…”
Section: Safety Of Celecoxibmentioning
confidence: 99%
“…This patient was diagnosed as H. pylori positive and was concurrently using the bisphosphonate alendronate for the prevention of steroid-induced osteoporosis. Bisphosphonates are known to cause GI damage when administered alone [33], and it has been reported that co-administration of bisphosphonates increases the incidence rate of NSAID-induced ulcers [34,35].…”
Section: Discussionmentioning
confidence: 99%